Gambaran Pengetahuan Ibu Hamil Tentang Program Perencanaan Persalinan dan Pencegahan Komplikasi - Ariani, Antri; Destyana, Adelia; Pragholapati, Andria (CV. Publikasi Indonesia, 2022)
Delivery Implementation and Complication Prevention (P4K) Program facilitated by village midwives in order to increase the active role of husbands, families and communities in planning safe deliveries and preparing for complications for pregnant women. P4K activities are collecting data and attaching stickers to pregnant women, birth attendants by health workers, delivery funds, village ambulances, post-delivery family planning and blood donation donations. P4K activities aim to reduce the Maternal Mortality Rate (MMR) which was recorded at 102 per live birth in 2015 and continues to increase by 359 per 100,000 live births. This study aims to describe the knowledge of pregnant women about the delivery planning program and prevention of complications at Puskesmas X. This research is a descriptive study that is about the description of knowledge of pregnant women about P4K.sampling technique was accidental sampling , with a population of 74 people. Data analysis used univariate analysis. The results showed that the knowledge of pregnant women about P4K was more than half of the respondents with less knowledge as much as 55.4%. Suggestions for the puskesmas are expected to increase understanding about P4K by providing information such as holding health counseling activities about P4K to pregnant women, husbands, cadres, and paraji shamans.